Ebenezer Howard Idea in the planning of Krakow. A short history - Motak, Maciej (International Planning History Society Proceedings, 2016)
Neither professional planner nor architect, Ebenezer Howard has remained an outstanding figure in the field of planning and, more generally, shaping the structure and image of contemporary cities. His Garden City notion has been used, or sometimes misused, in numerous projects, quotations, references and other forms of attention being paid. Howard’s 1898 publication became known to Polish readers, through reviews, as early as in 1899. In 1912 Howard paid a brief visit to Krakow. He delivered a lecture there and, after having gained some site orientation, issued comments on Krakow urban development. His calling Krakow ”a garden city from natural growth” was proudly quoted in there. Since Howard had fully published his concept and visited the city, Krakow faced a number of challenges which added new stages to its thousand-year-long development history and resulted in new urban forms and heritage. In 1918 the city ceased to be powerful Austrian fortress it had been since 1850, while the 1909-1915 eight-fold enlargement resulted in substantial opportunities of development on vast “Great Krakow” areas. Its harmonious urban development during the Polish Second Republic (1918-1939) was broken by the World War II and Nazi occupation (1939-1945). The city’s rapid growth in the communist Poland (1945-1989) started in 1949 with the construction of Nowa Huta, a planned “Socialist” city next to Krakow and continued until 1988 with numerous Modernist housing projects and industrialization. Since in 1989-1990 market economy and self-government were restored in Poland, the city, despite unaltered area and population figures, has been turning into a metropolitan centre through intensification and thorough transformations. It could be initially expected that, like most new theories, Howard’s ideas would sink into oblivion in Krakow. However, they have never been entirely forgotten. Some of the urban challenges were responded with the solutions influenced by the Garden City concept. Although the attempts to link the Salwator Hill housing project (1908) with Howard’s ideas have already been proved impossible, some of the Interwar Period projects, especially the Officers’ Neighbourhoods (planned in 1924-1932), based on the regulation plans, seem to have been inspired by the Garden City. Another case can be found in the first neighbourhoods of Nowa Huta, which had been designed in 1949 before the Socialist Realism doctrine fully took over until 1955. And recently Garden City seems to be a notion appreciated by potential customers and therefore used in advertisements on new housing projects, however that usually differs from what Howard actually meant. The article deals with direct and indirect impact of Howard’s concept upon Krakow urban development in particular periods. According to the research the extent of Garden City concept’s influence was weakening with time. The range of effects and the number of examples of Garden-City-related approach was limited. Moreover, the popularity of Howard’s concept did not necessarily mean sharing his original views. Finally, it would be less justified to call Krakow “the garden city from natural growth” nowadays than over a hundred years ago.